2021
DOI: 10.3389/frobt.2020.541741
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Industrial Collaborative Robots by People With Disabilities in Sheltered Workshops

Abstract: The integration of people with disabilities into the working world is an important, yet challenging field of research. While different inclusion efforts exist, people with disabilities are still under-represented in the open labor market. This paper investigates the approach of using a collaborative robot arm to support people with disabilities with their reintegration into the workplace. However, there is currently little literature about the acceptance of an industrial robot by people with disabilities and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
20
1
1
Order By: Relevance
“…In most of the articles, technology (see Table 1) was conceived as a useful tool for performing a task [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and/or for the reduction of a physical [41,42,45,47,53,55,59,60], cognitive [43,44,48,49,54,56,[61][62][63][64][65], or mental health [66] accommodation/participation [48,[50][51][52]54,56,57,60,64,65,[67][68]…”
Section: Systematic Review (Step 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the articles, technology (see Table 1) was conceived as a useful tool for performing a task [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and/or for the reduction of a physical [41,42,45,47,53,55,59,60], cognitive [43,44,48,49,54,56,[61][62][63][64][65], or mental health [66] accommodation/participation [48,[50][51][52]54,56,57,60,64,65,[67][68]…”
Section: Systematic Review (Step 1)mentioning
confidence: 99%
“…Only a few cases discussed the impact of technology use on financial issues [76], employment inclusion [70], identity [67,77], self-determination/empowerment [43,[78][79][80], and ethical issues [81]. The different forms concerned the use of AT as mobile support tools [42,47,51,61,65,66], cognitive assistance systems [41,43,44,70], apps or technological devices [49,53,65,66,74], robotics [45], brain-computer interface [55], social media [69,80], eHealth [68], information and communication technologies (ICTs) [52,63,78,79], and virtual reality (VR) [59,71,72,77].…”
Section: Systematic Review (Step 1)mentioning
confidence: 99%
“…Robotic assistance is generally well-received by people with motor impairments. Drolshagen et al found that people with disabilities quickly accept working with robots, even if the robots are in close proximity [19]. Regarding ADLs specifically, Pascher et al conducted an ethnographic study with 15 participants with tetraplegia, multiple sclerosis, Locked-In Syndrome, and similar diseases [20].…”
Section: Related Workmentioning
confidence: 99%
“…Both found that robotic devices are often designed to assist with several different activities of daily living, often resulting in larger robotic devices that frequently require a robotic arm mounted on a mobile unit. Drolshagen et al investigated the acceptance of robots in sheltered workshops, finding that robots are quickly accepted and close proximity is preferred [26]. Currently, a trend can be observed towards the research into cobots in domestic care to support people in their everyday lives [27][28][29][30][31][32].…”
Section: Cobots For Carementioning
confidence: 99%